Change of interferons ? and ? levels in the blood of patients with uveitis as a result of combination therapy with the use of cycloferon, decametoxine electrophoresis and microwave therapy - N.V. Konovalova; Chaibi Abderrahim (Ukrainian Society of Ophthalmologists, 2015)
Introduction. Searching for new effective pathogenetic approaches to the uveitis treatment is both clinically and socially relevant, considering the pathology high prevalence and disease-induced disability. Objective. To determine the peculiarities of interferons ? and ? expression in the blood of patients with uveitis as a result of combination therapy with the use of cycloferon, decametoxine electrophoresis and microwave therapy. Materials and methods. Patients with endogenous uveitis received a combination therapy with the use of cycloferon, decametoxine electrophoresis and microwave therapy (26 persons). Control groups: cycloferon and decametoxine electrophoresis (20 persons) and cycloferon and microwave therapy (13 persons). The level of interferons ? and ? was measured in the blood plasma and the ophthalmological examination was carried out before and after the treatment. Parametric and nonparametric criteria, as well as correlation analysis, were used in statistical data processing. Results. A significant increase of interferons ? and ? concentration was found as a result of the treatment of patients with uveitis. The increase degree does not depend on the focus of inflammation location and the nature of the clinical course. At the same time, the most significant increases are pronounced the most in severe uveitis. There was found a reliable correlation between the level of interferons before and after the treatment, as well as the clinical characteristics of the disease. The increase of interferons ? and ? level was determined in various clinical forms of uveitis. The most pronounced increase of interferons ? and ? level was detected as a result of decametoxine electrophoresis and microwave therapy on the background of cycloferon administration. It amounts 56.7% and 33.4% respectively. Conclusions. The increase of interferons level was detected in the blood of patients after the treatment. The most significant increase occurred as a result of decametoxine electrophoresis and microwave therapy on the background of cycloferon administration. It may be considered as one of the treatment efficacy criteria.